2007
DOI: 10.1158/1055-9965.epi-06-0942
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Prostate Cancer through Dietary Agents: Progress and Promise

Abstract: Prostate cancer (CaP) is second only to lung cancer as the cause of cancer-related deaths in American men and is responsible for over 29,000 deaths per year. One promising approach to reduce the incidence of CaP is through chemoprevention, which has been recognized as a plausible and cost-effective approach to reduce cancer morbidity and mortality by inhibiting precancerous events before the occurrence of clinical disease. Indeed, CaP is an ideal candidate disease for chemoprevention because it is typically di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
125
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 95 publications
3
125
0
3
Order By: Relevance
“…In addition, it is becoming increasingly appreciated that cancer chemoprevention through the use of naturally occurring dietary agents may be an effective strategy for the management of PCa. (2,4,5). Consistent with the idea of chemoprevention there has been a growing increase to use dietary supplements by PCa patients to alleviate disease.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, it is becoming increasingly appreciated that cancer chemoprevention through the use of naturally occurring dietary agents may be an effective strategy for the management of PCa. (2,4,5). Consistent with the idea of chemoprevention there has been a growing increase to use dietary supplements by PCa patients to alleviate disease.…”
Section: Introductionmentioning
confidence: 95%
“…In the absence of satisfactory treatment options for PCa, chemoprevention could be an effective approach to reduce the incidence of the disease, an area of investigation which we recently reviewed (6 and the references therein). PCa represents an ideal candidate disease for chemoprevention because it is diagnosed in elderly males; thus even a moderate delay in the neoplastic changes achieved through pharmacologic or dietary intervention could result in a substantial reduction in the incidence of the clinically detectable disease (6)(7)(8). There is currently intense effort in identifying mechanism-based naturally occurring agents present in diet and beverages consumed by humans for their cancer chemopreventive and possibly cancer therapeutic efficacy against PCa (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…PCa represents an ideal candidate disease for chemoprevention because it is diagnosed in elderly males; thus even a moderate delay in the neoplastic changes achieved through pharmacologic or dietary intervention could result in a substantial reduction in the incidence of the clinically detectable disease (6)(7)(8). There is currently intense effort in identifying mechanism-based naturally occurring agents present in diet and beverages consumed by humans for their cancer chemopreventive and possibly cancer therapeutic efficacy against PCa (6)(7)(8)(9). The identification of new predictive biomarkers will be important for improving clinical management, outcome of treatment protocols, and assessing the effectiveness of chemopreventive regimens, all of which could lead to improved survival of patients with the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Cancer Society estimates that 28,660 men in the United States will die of Prostate Cancer in 2008 and accounts for about 9% of cancer related deaths in men (American Cancer Society, 2008). The epidemiological studies have shown significant correlations between prostate cancer incidence and dietary habits and the potential of dietary substances to act as chemopreventive agents against prostate cancer is increasingly appreciated (Syed et al, 2007(Syed et al, : 2008. In this regard long-term well-designed and optimized intervention trials are required to delineate the potential clinical usefulness of C. longa both in normal populations as well as in high-risk groups and warrant further studies in the treatment and prevention of human neoplasm.…”
Section: Introductionmentioning
confidence: 99%